2016
DOI: 10.1159/000444545
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Management of Alcoholic Liver Disease

Abstract: Alcoholic liver disease (ALD) is a leading cause of liver-related morbidity and mortality. ALD encompasses a spectrum of disorders ranging from asymptomatic steatosis, alcoholic steatohepatitis, fibrosis, cirrhosis and its related complications. Moreover, patients can develop an acute-on-chronic form of liver failure called alcoholic hepatitis (AH). Most patients are diagnosed at advanced stages of the disease with higher rates of complications and mortality. The mainstream of therapy of ALD patients, regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 59 publications
0
31
0
9
Order By: Relevance
“…Alcoholic liver disease is one of the most serious medical consequences of chronic ethanol use[ 1 , 2 ]. Investigations into the mechanisms of ethanol-induced liver injury have revealed that chronic ethanol abuse causes alterations in the methionine metabolism[ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alcoholic liver disease is one of the most serious medical consequences of chronic ethanol use[ 1 , 2 ]. Investigations into the mechanisms of ethanol-induced liver injury have revealed that chronic ethanol abuse causes alterations in the methionine metabolism[ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alcoholic liver disease (ALD) is an alcohol-associated pathologic process characterized by a range of liver disorders from steatosis, steatohepatitis, hepatitis, fibrosis/ cirrhosis, to hepatocellular carcinoma and liver failure. 1,2 Studies in rodents and humans have demonstrated that excessive alcohol consumption induces pathophysiological conditions in multiple organs. Ethanol-induced liver dysfunctions are driven by organ crosstalk via intestineeliver, adiposeeliver, or adiposeeintestine-liver axis.…”
mentioning
confidence: 99%
“…1e3 Alcohol intake induces liver dysfunction by breaking barrier integrity and function of small intestine and by promoting growth of intestinal pathogenic bacteria and harmful metabolites (eg, lipopolysaccharides). 1,2 Ethanol exposure damages the liver by impairing fibroblast growth factor (FGF) 15/19, an ileum-derived hormone, and by disrupting FGF 15/19-mediated signaling. 4e6 Altered intestinal microbiota and abnormal bile acid metabolism are also involved in the pathogenesis of ALD.…”
mentioning
confidence: 99%
“… 69 Moreover, steatosis is rapidly resolved by abstinence, which remains a mainline therapy for ALD and AH, and, thus, the likelihood that addressing liver steatosis as an effective therapeutic target for AH is minimal, as it is self-resolving in compliant patients. 70 , 71 …”
Section: Alcoholic Liver Disease In the Mouse – Limited Pathologymentioning
confidence: 99%